2018
DOI: 10.1080/03057240.2017.1415871
|View full text |Cite
|
Sign up to set email alerts
|

Life goals of Finnish social services students

Abstract: Her research interests include service learning, social pedagogical education, interactional and intercultural competencies, purpose and relationship-based social services work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…The majority of students in all profiles indicated that they wanted to lead a happy and pleasurable life. This finding is in line with the previous study, which found that Finnish students in social services rate hedonistic goals, such as leading an exciting life, rather highly (Manninen et al, 2018a). Also in all profiles, approximately a half of the students desired to be a good person or lead a good life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of students in all profiles indicated that they wanted to lead a happy and pleasurable life. This finding is in line with the previous study, which found that Finnish students in social services rate hedonistic goals, such as leading an exciting life, rather highly (Manninen et al, 2018a). Also in all profiles, approximately a half of the students desired to be a good person or lead a good life.…”
Section: Discussionsupporting
confidence: 92%
“…In practice this means that they do not know why they are engaged in prosocial activities such as pursuing a helping profession; neither can they identify what are the implications of these activities for oneself or others. Purposeful individuals on the other hand have identified their personally meaningful higher-order long-term life goals, which they justify with reference to personal and prosocial benefits (Moran, 2009; see also Manninen et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Social and religious goals did not seem as important for Iranian students as economic and hedonistic goals, a finding that contrasts with the ultimate goal of the Iranian educational system. This finding accords with research in Western countries where helping others is related more to personal well-being and career aspirations than to religious life goals (Manninen, Kuusisto, & Tirri, 2017). However, the association between helping others in need with religiousness and community volunteer work reflects one of the five pillars Muslims should follow in their daily lives (Rasool, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…were analysed deductively by utilizing Robert andRobins's (2000, Hedayati et al, 2017b;Manninen et al, 2018) categories and inductively by creating subcategories based on the data. whereas 'Emotional support' appeared only 3 times (Table 5.6).…”
Section: Contents Of the Purposesmentioning
confidence: 99%